Virtual unbundling: The basis for competition in next generation access networks? - Wolfgang Reichl; Ernst-Wolfgang Ruhle; Martin Lundborg; Matthias Ehrler (International Telecommunications Society (ITS), 2012)
Next Generation Access Networks will enable much higher bandwidths than copper based access networks. Although technological progress provides for higher bandwidth on copper as well, most experts agree that next generation access networks finally will be based on fibre optic cables in the entire or part of the access networks. In order to accomplish the migration towards Next Generation Access Networks, high investment is needed and various models for co-operation and co-financing are tried out worldwide. What does the deployment of fibre optic cables in the access networks mean for the wholesale market and competition? Unbundling of copper cables has been the basis for infrastructure based competition in telecommunications networks especially in the European environment for more than a decade. Unbundling of fibre is an option in case of point to point architectures. Current solutions of Fibre-to-the-Curb and Fibre-to-the-Building technologies rely of sharing of fibre infrastructures and make physical unbundling cumbersome. Does this mean the end of physical unbundling and is bitstream access the wholesale product of the future?
Keywords: 330